The territoriality, vocalizations and aggressive interactions of the red-spotted glassfrog, Nymphargus grandisonae, Cochran and Goin, 1970 (Anura: Centrolenidae) - Hutter, Carl (2013)
In many frog species, males defend a territory through direct male-to-male interactions and/or aggressive calling behaviour. We describe the site fidelity, vocalizations, aggressive interactions, and male combat behaviour of the glassfrog Nymphargus grandisonae. We show high specificity of males' calling and mating sites. We then describe the temporal and spectral differences for six types of vocalizations. We link these vocalizations to behavioural observations, describing their aggressive and reproductive contexts. Additionally, we show that combat is highly variable and includes three previously described and two unreported variations. We describe injuries resulting from combat and we report the first observation of a multiple night fight between the same two males. Our observations on site fidelity and aggression provide evidence for territoriality among males. Furthermore, our results suggest that combat behaviour in glassfrogs is more complex than previously hypothesized and that hypotheses on the evolution of combat behaviour need re-evaluation. © 2013 © Taylor & Francis.